Evaluating the effect of waste glass on the fresh and mechanical properties of mortar: A review - Ahmad, Soran Abdrahman; Rafiq, Serwan Khurshid (Sulaimani Journal for Engineering Sciences, 2022)
During quick developing and increasing the requirement of the human life, with the progressing civilization in history, glass instruments (different types, sizes, shapes, and equipment) were one of the helpful parameters in human life. With increasing population and developing equipment, increase the production of glass in the world and recycling of waste glass become one of the main subjected by researchers to develop a quick and economic way to reuse waste glass especially color glass. This article includes a review of previous work for using a different type of waste glass (cathode ray tube, heavy glass, food, medical glass, door and window's glass, spent fluorescent glass, color and un-color glass) as a replacement to fine aggregate in mortar and showing its effect on the fresh and mechanical properties of mortar. The results show that, based on the chemical composition and grinding of particles had a different effect on the early and mechanical properties. The optimum percentage range of using waste glass which can provide property near to control mix vary between 20-30%. The effect of glass granular on fresh and mechanical properties of the mortar is dependent on the particle grading and its chemical composition in which, when 25% of waste glass from brawn bottle used in mortar increase 10% in compressive strength and decrease flexural strength by 6% while using 25% of heavy weight waste glass decrease 10% of compressive strength and 9% of flexural strength of the mortar.
Keywords: Compressive strength; flow; flexural strength; mortar; sand replacement; waste glass